Bed load sediment transport in the presence of vegetation - Choon, Hui Xun (2017)
This report aims to find out the effect of vegetation on sediment transport rates in water. This will aid in reality to prevent soil and bank erosion at natural water sources like rivers, inhibiting possible water pollution. Laboratory experiments were conducted under controlled variables of energy gradient, grain size and channel size while varying factors such as water discharge, critical velocity, water depth and bed-form characteristics to obtain values of sediment transport rates. These rates are then compared to theoretical transport rates calculated, which do not factor in the effect of vegetation on the sand bed. The study reveals that the presence of vegetation impedes the rate of transport of sediment due to the obstruction posed by the vegetation. This is useful in the case of Singapore, where majority of water bodies are used for potable purposes and the presence of vegetation would aid in increasing the sterility of these water bodies from sediments transported due to water flow.